Light perception in two strictly subterranean rodents: life in the dark or blue? - Kott, Ondrej; Sumbera, Radim; Nemec, Pavel (PloS one, 2010)
BACKGROUND: The African mole-rats (Bathyergidae, Rodentia) are strictly subterranean, congenitally microphthalmic rodents that are hardly ever exposed to environmental light. Because of the lack of an overt behavioural reaction to light, they have long been considered to be blind. However, recent anatomical studies have suggested retention of basic visual capabilities. In this study, we employed behavioural tests to find out if two mole-rat species are able to discriminate between light and dark, if they are able to discriminate colours and, finally, if the presence of light in burrows provokes plugging behaviour, which is assumed to have a primarily anti-predatory function. METHODOLOGY/PRINCIPAL FINDING: We used a binary choice test to show that the silvery mole-rat Heliophobius argenteocinereus and the giant mole-rat Fukomys mechowii exhibit a clear photoavoidance response to full-spectrum ("white"), blue and green-yellow light, but no significant reaction to ultraviolet or red light during nest building. The mole-rats thus retain dark/light discrimination capabilities and a capacity to perceive short to medium-wavelength light in the photopic range of intensities. These findings further suggest that the mole-rat S opsin has its absorption maximum in the violet/blue part of the spectrum. The assay did not yield conclusive evidence regarding colour discrimination. To test the putative role of vision in bathyergid anti-predatory behaviour, we examined the reaction of mole-rats to the incidence of light in an artificial burrow system. The presence of light in the burrow effectively induced plugging of the illuminated tunnel. CONCLUSION/SIGNIFICANCE: Our findings suggest that the photopic vision is conserved and that low acuity residual vision plays an important role in predator avoidance and tunnel maintenance in the African mole-rats.
Keywords: mikroftalmičtí podzemní hlodavci; Behavior, Animal; světlo; chování zvířat; krysa rodu Rattus; Mole Rats; Animals; Light; Rats; zvířata; Visual Perception; zraková percepce